(3GdThGQO hGdThGgOs ((3eUQ s)
(3ChdgG (B:s
(3GeG HYO , aEf GdCOH CTQa fSH , haVd CUd , hCLd eGd , hCJe LeGd , hEf GdCOH s
(3BNQgG (B:s
(3hGddKje JfSjI Ndg hGMOI Cda Ndg ef GdEMSGf Ke cJGH s
(3fbdG Yf GdfSNI GdChdi ef GdcJGHs
(3cJH Sfg (B561(3g` ai gePGf ai OGQ GdejQ fLe GdOjf Sja GdESdGe jQJbT GdSYOi GdcQLis
(3hHBNQ UaMGJgG JYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs